The Effect of Capital Structure On Company Value with Profitability and Dividend Policy as A Mediating Variable - A. A. Ayu Tirtamara; Luh Gede Sri Artini (Return : Study of Management, Economic and Bussines, 2024)
The theory of capital structure with taxes is put forward by stating that the value of a company increases as the total debt increases. The use of debt in the company's capital structure, on the other hand, also incurs costs that can reduce the value of the company, so Modigliani and Miller (1963) the trade-off theory reveals that there is a so-called optimal capital structure. This study aims to test and analyze the influence of capital structure, profitability, and dividend policy on company value, both directly and indirectly. The population of this study is pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the period 2008-2022. The sampling technique used was the purposive sampling technique and samples were obtained from 6 companies with a total of 90 years of observation. This study uses secondary data in the form of annual financial statements of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2008-2022 period. The data analysis technique in the study uses the dynamic panel method of the system generalized method of moments (GMM) with the Rstudio application. The results of the analysis provide evidence that capital structure, profitability, and dividend policy have a significant positive effect on the company's value. Capital structure has a significant positive effect on profitability and dividend policy. Capital structure affects the value of the company through profitability as a mediating variable. Capital structure affects the value of the company through dividend policy as a mediating variable. Company management is advised to always maintain an optimal capital structure for the company so that it can increase profitability and dividend distribution so as to increase the company's value. For the next researcher, it is recommended to increase the number of research samples so that the research results can be generalized widely.